2019
DOI: 10.3390/microorganisms7090295
|View full text |Cite
|
Sign up to set email alerts
|

Elizabethkingia Infections in Humans: From Genomics to Clinics

Abstract: The genus Elizabethkingia has recently emerged as a cause of life-threatening infections in humans, particularly in immunocompromised patients. Several new species in the genus Elizabethkingia have been proposed in the last decade. Numerous studies have indicated that Elizabethkingia anophelis, rather than Elizabethkingia meningoseptica, is the most prevalent pathogen in this genus. Matrix-assisted laser desorption/ionization–time of flight mass spectrometry systems with an extended spectrum database could rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
187
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(194 citation statements)
references
References 69 publications
(207 reference statements)
3
187
2
2
Order By: Relevance
“…In previous reports, the case fatality rate of patients with E. anophelis infection ranged from 24-60% in different countries [4][5][6][7][8][9][10][11][12][13][14]. In line with this, our study showed that the in-hospital mortality rate of patients with an E. anophelis infection was 51.3%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In previous reports, the case fatality rate of patients with E. anophelis infection ranged from 24-60% in different countries [4][5][6][7][8][9][10][11][12][13][14]. In line with this, our study showed that the in-hospital mortality rate of patients with an E. anophelis infection was 51.3%.…”
Section: Discussionsupporting
confidence: 87%
“…Thereafter, the prevalence of E. anophelis infections has been rampant; it is the primary species of Elizabethkingia genus infections that have recently occurred in Singapore [3], Hong Kong [4], the United States [5,6,7,8], South Korea [9] and Taiwan [10]. E. anophelis is an important opportunistic pathogen associated with various invasive infections in adults with underlying diseases and infants (premature and neonates) [11,12]. Several outbreaks have occurred in Singapore and in the Midwestern United States of Wisconsin, Illinois, and Michigan, where the fatality rate of patients with E. anophelis infections ranged from 30-60% [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The reports varied on the susceptibility of Elizabethkingia isolates against fluoroquinolones. 32 Favored in vitro activity of fluoroquinolones was observed in this study, and the susceptibility rate for levofloxacin was higher than that for ciprofloxacin. By contrast, fluoroquinolones exhibited poor activity against E. anophelis and E. meningoseptica while all E. miricola isolates were susceptible to levofloxacin and moxifloxacin in a hospital in South Korea.…”
Section: Discussionmentioning
confidence: 45%
“…18,20 In this study, we also found that the identification for Emi007 was ambiguous with 16S rRNA gene sequencing, which could be partly explained by the existence of multiple copies with different sequences and the hypervariable regions of 16S rRNA. 32 It has been pointed out that the rpoB gene is a single copy gene and has a higher resolution of phylogenetic evolution than the 16S rRNA gene; thus, it could accurately distinguish Elizabethkingia strains at the species level. 7,32 PFGE profiles showed finer resolution of clonal relationships, indicating that Emi007 was genetically more related to Emi099 than Emi088 with a similarity of 81.1%, thereby supporting its identity as E. miricola.…”
Section: Discussionmentioning
confidence: 99%
“…It is often characterized by its "dumbbell" shape. 36 Like Chryseobacterium, Elizabethkingia species may appear thin, long, and slightly curved on gram stain. The bacterium was discovered in 1959 by Elizabeth O.…”
Section: Introductionmentioning
confidence: 99%